Analisis Aplikasi Mobile Banking Jenius Menggunakan Metode Technology Acceptance Model (TAM) Di Kota Jambi - Cipta Hadi, Denny Setya; Assegaff , Setiawan (Jurnal Manajemen Sistem Informasi, 2022)
Bank BTPN is one of the private conventional banks in Indonesia. In carrying out business processes, Bank BTPN has developed the Jenius mobile banking application system where the application can make it easier for Bank BTPN customers to conduct financial transactions. However, in the development of the application, there are still many shortcomings and the level of doubt for Bank BTPN customers to use the application is still high. Therefore, a study was conducted to determine the level of trust of Bank BTPN customers in using the application. In this study, behavioral analysis theory was used, namely the Technology Acceptance Model (TAM) theory which was assisted by the Smart PLS application for the analysis process. The results of this study consist of 4 variables including Complexity Of Use, Perceived Usefullness, Perceived Of Use and Intention To Use. The results of the study explain that customers are quite good at accepting the Jenius mobile banking application and the level of customers to continue using the application is also good. The results of the research can be used as a reference to continue developing the Jenius mobile banking application to be even better. It is hoped that in the future similar research can be carried out to find out the potential for the development of the Jenius mobile banking application.